Building climate resilience in degraded agricultural landscapes through water management: A case study of Bundelkhand region, Central India - Garg, K.K.; Singh, R.; Anantha, K.H.; Singh, A.K.; Akuraju, V.R.; Barron, Jennie; Dev, I.; Tewari, R.K.; Wani, S.P.; Dhyani, S.K.; Dixit, S. (Elsevier, 2020)
Rainfall variability and water scarcity continue to hamper the food and income security of smallholder farming systems in poverty-affected regions. Innovations in soil and water management, especially in the drylands, are critical for meeting food security and water productivity targets of Agenda 2030. This study analyzes how rainfed agriculture can be intensified with marginal impact on the landscape water balance. The impact of rainwater harvesting structures on landscape hydrology and associated agricultural services was analyzed in the semi-arid Jhansi district of Bundelkhand region in central India. The Parasai-Sindh pilot watershed was subjected to a 5-year (2012–2016) monitoring of rainfed system improvements in water availability and crop intensification due to surface water storage (haveli system), check dams, and field infiltration structures. Hydrological processes were monitored intensively to analyze the landscape’s water balance components. Rainwater harvesting (RWH) structures altered the landscape’s hydrology, limiting average surface runoff from 250 mm/year to 150 mm/year over the study period. Groundwater levels increased by 2–5 m (m), alleviating water scarcity issues of the communities in recurring dry years. Nearly 20% of fallow lands were brought under cultivation. Crop yields increased by 10–70% and average household income increased from US$ 960/year to US$ 2700/year compared to that in the non-intervention landscape. The combined soil–water–vegetation efforts strengthened water resilience and environmental systems in agricultural landscape.